2005
DOI: 10.1111/j.1085-9489.2005.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Large and small fiber neuropathy in chronic alcohol‐dependent subjects

Abstract: The aim of the present study was to evaluate the occurrence of large and small fiber neuropathy among alcohol-dependent subjects and to correlate neuropathy with the pattern of alcohol abuse, age of the subjects, nutritional status, and biochemical parameters. The study sample comprised 98 consecutive alcohol-dependent subjects without signs of malnutrition treated for detoxification voluntarily in the specialized unit of the Athens University Psychiatric Clinic in an inpatient basis. Polyneuropathy (PN) was g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
1
8

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 25 publications
3
73
1
8
Order By: Relevance
“…On electromyography distal denervation is seen. These studies are often abnormal in the presymptomatic patient [11]. In patients with chronic alcoholism combined with thiamine deficiency, CMAPs are more severely reduced [7].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations
“…On electromyography distal denervation is seen. These studies are often abnormal in the presymptomatic patient [11]. In patients with chronic alcoholism combined with thiamine deficiency, CMAPs are more severely reduced [7].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The incidence of alcoholic polyneuropathy according to gender is controversial: according to Ammendola et al [4] it is higher in women than in men, Zambelis et al [11] found the reverse. The total lifetime amount of alcohol consumption and the duration of alcohol abuse are associated with ALN [3,11]. ALN is more prevalent in frequent, heavy, and continuous drinkers than in episodic drinkers [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Western hemisphere, alcoholic peripheral neuropathy is most www.journalchiromed.com prevalent in the 40-to 70-year-old age group and is encountered in both men and women. 1,2 Long-term excessive alcohol consumption affects the peripheral and autonomic nervous systems. 1 Severe alcoholic polyneuropathy may cause difficulty walking, frequent falls, or paralysis.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Long-term excessive alcohol consumption affects the peripheral and autonomic nervous systems. 1 Severe alcoholic polyneuropathy may cause difficulty walking, frequent falls, or paralysis. 3 Spasticity is a state of hypertonicity with exaggeration of the tendon reflexes mediated by a loss of inhibitory control of the upper neurons.…”
Section: Introductionmentioning
confidence: 99%